Bias in Student Ratings of Instruction: A Systematic Review of Research from 2012 to 2021 - Stoesz, Brenda M.; De Jaeger, Amy E.; Quesnel, Matthew; Bhojwani, Dimple; Los, Ryan (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
Student ratings of instruction (SRI) are commonly used to evaluate courses and teaching in higher education. Much debate about their validity in evaluating teaching exists, which is due to concerns of bias by factors unrelated to teaching quality (Spooren et al., 2013). Our objective was to identify peer-reviewed original research published in English from January 1, 2012, to March 10, 2021, on potential sources of bias in SRIs. Our systematic review of 63 articles demonstrated strong support for the continued existence of gender bias, favoring male instructors and bias against faculty with minority ethnic and cultural backgrounds. These and other biases must be considered when implementing SRIs and reviewing results. Critical practices for reducing bias when using SRIs include implementing bias awareness training and avoiding use of SRIs as a singular measure of teaching quality when making decisions for teaching development or hiring and promotion.